Knockdown of NRSF Alleviates Ischemic Brain Injury and Microvasculature Defects in Diabetic MCAO Mice - He, Cheng-Feng; Xue, Wen-Jiao; Xu, Xiao-Die; Wang, Jian-Tao; Wang, Xin-Ru; Feng, Yi; Zhou, Hou-Guang; Guo, Jing-Chun (Frontiers in Neurology, 2022)
Diabetes is one of the well-established risk factors of stroke and is associated with a poor outcome in patients with stroke. Previous studies have shown that the expression of neuron restrictive silencer factor (NRSF) is elevated in diabetes as well as ischemic stroke. However, the role of NRSF in regulating an outcome of diabetic ischemic stroke has not been completely understood. Here, we hypothesized that diabetes-induced NRSF elevation can aggravate brain injury and cognition impairment in ischemic stroke. The diabetic ischemic stroke mice model was established by 8 weeks of high-fat-diet feeding and 5 days of streptozotocin injection followed by 30 min of middle cerebral artery occlusion (MCAO). We found that diabetes enhanced the MCAO-induced elevation of NRSF in the hippocampus in accompany with an elevation of its corepressors, HDAC1, and mSin3A, and decrease of β-TrCP. By using histological/immunofluorescence staining and neurobehavioral testing, our results showed that the brain damage and learning/memory impairment were aggravated in diabetic ischemic mice but significantly attenuated after stereotaxic injection of NRSF-shRNA. Meanwhile, by performing whole-brain clearing with PEGASOS, microvascular reconstruction, western blotting, and ELISA, we found that NRSF-shRNA markedly alleviated the vasculature disorders and rescued the suppression of NRP-1, VEGF, and VEGFR2 in the hippocampus of diabetic ischemic mice. Therefore, our results demonstrated for the first time that the elevation of hippocampal NRSF plays an important role in alleviating brain injury and cognitive disabilities in diabetic ischemic mice, potentially via the reduction of NRP-1/VEGF signaling.